The Inheritance of Anaphylactic Sensitivity in Mice using Bovine Plasma Albumin as an Antigen - Sobey, W. R. (1959)
Using bovine plasma albumin as an antigen anaphylactic sensitivity was found to be highly heritable, h(2)=0.92 (0.54 to 1.0).